A contribution to the study of a manorial right in the medieval lands of Alcobaça: the montado dos porcos - Gonçalves, Iria (2017)
Among the manorial rights collected by the monastery of Alcobaça were those that could be gathered upon the fruition of the uncultivated lands, particularly the forests, given the range of the potential that such areas had and could offer. Among those rights, one of the most important was the payment of the montado, which in Alcobaça impended only upon the pasture of pigs in the manor woods during the period known as montanheira, between September and January. Omitted in the primitive charters granted by the monastery to its villages, this tax was developed just by the middle of the fourteenth century, giving rise to a long conflict with the local communities, only solved by the new charters of the sixteenth century.   Bibliography Handwritten sources Arquivo Nacional da Torre do Tombo (TT)Ordem de Cister, Mosteiro de Santa Maria de Alcobaça– livros 3, 5, 10, 12, 15, 136, 183, 212.– 1ª incorporação, maços 32, 35, 37, 39, 42.– 2ª incorporação, maços 1, 2, 26, 29, 38, 46, 48, 49, 58, 62, 64, 70, 86.   Printed sources ACTAS DE VEREAÇÃO de Loulé. Século XV. supl. de Al’-Ulyā, n.º 10. Loulé: Arquivo Histórico Municipal de Loulé, 2004. CHANCELARIA DE D. AFONSO III. Ed. Leontina Ventura e António Resende de Oliveira. Liv. I, vol. 1. Coimbra: Imprensa da Universidade de Coimbra, 2006. FERNANDES, Rui – Descrição do terreno ao redor de Lamego duas léguas [1531-1532]. Ed. crítica de Amândio Morais Barros. Lamego: Beira Douro, 2001. FORAIS MANUELINOS do reino de Portugal e do Algarve conforme o exemplar do Arquivo Nacional da Torre do Tombo de Lisboa - Estremadura. Ed. por Luiz Fernando de Carvalho Dias. Lisboa: L. F. C. Dias, 1962. HISTÓRIA FLORESTAL, aquícola e cinegética. Colectânea de documentos existentes no Arquivo Nacional da Torre do Tombo. Chancelarias Reais. Ed. Carlos Manuel L. Baeta Neves, vol. II (1439-1481). Lisboa: Ministério da Agricultura, Comércio e Pescas – Direcção-Geral das Florestas, 1982. LIVRO DA VEREAÇÃO de Alcochete e Aldeia Galega (1421-1422). Introdução, transcrição e notas de José Manuel Vargas. Alcochete: Câmara Municipal de Alcochete, 2005. LIVRO DAS POSTURAS ANTIGAS. Leitura paleográfica e transcrição de Maria Teresa Campos Rodrigues. Lisboa: Câmara Municipal de Lisboa, 1974. “LIVRO DAS POSTURAS ANTIGAS de Évora”. [Transcrição de] Ana Sesifredo, Fátima Farrica e Miguel Meira. in Posturas municipais portuguesas (séculos XIV-XVIII). Ponta Delgada: Centro de Estudos Gaspar Frutuoso, 2012, pp. 27-116. “O LIVRO DAS POSTURAS DA VILA de Abrantes de 1515”. Ed. com nota explicativa de J. Candeias Silva. in Abrantes – Cadernos para a história do município, 1 (1982), pp. 69-94. POSTURAS DO CONCELHO de Lisboa (século XIV). Apresentação de Francisco José Veloso, leitura paleográfica, nótula e vocabulário de José Pedro Machado. Lisboa: Sociedade de Língua Portuguesa, 1974. VEREAÇÕES DA CÂMARA Municipal do Funchal, vol. II, Primeira metade do século XVI. Ed. por José Pereira da Costa. Funchal: Secretaria Regional do Turismo e Cultura, 1998.   StudiesALFONSO ANTÓN, Isabel – La colonización cisterciense en la meseta del Duero. El dominio de Moreruela (siglos XII-XIV). Zamora: Instituto de Estudios Zamoranos Florián de Ocampo – Diputación Provincial de Zamora, 1986. ALMEIDA, Fortunato de – História da Igreja em Portugal. 2.ª ed., org. por Damião Peres, vol. IV. Porto-Lisboa: Portucalense Editora, 1971. ARGENTE DEL CASTILLO OCAÑA, Cármen – La ganadería medieval andaluza. Siglos XIII-XVI (Reinos de Jaén y Córdoba). Jaén: Diputacón Provincial de Jaén, 1991. BARBOSA, Pedro Gomes – Povoamento e estrutura agrária da Estremadura Central. Séc. XII a 1325. Lisboa: INIC, 1992. BARROS, Henrique da Gama – História da administração pública em Portugal nos seculos XII a XV. 2ª ed. org. por Torquato de Sousa Soares, t. IX. Lisboa: Livraria Sá da Costa, 1950. BARUZZI, Marina; MONTANARI, Massimo – Porci e porcari nel Medioevo. Paesaggio, economia, alimentazione. Bolonha: Museo della Civilita Contadina, 1981. BECK, Corinne – “Animal et vie quotidienne en France et en Italie d’après les vestiges ostéologiques (XIème-XVème siècles)”. in Le monde animal et ses representations au Moyen Âge, (XIe-XVe siècles). Actes du XVème Congrès de la Société des historiens médiévistes de l’enseignement supérieur public, Toulouse, 25-26 mai 1984. Toulouse: Publications de l’Université de Toulouse-Le Mirail, 1985, pp. 103-120. BERTHE, Maurice – Famines et épidemies dans les campagnes navarraises à la fin du Moyen Âge, 2 vols., Paris: SFIED, 1984. BIASOTTI, Mirella; ISETTI, Paola – “L’alimentazione dall’ osteologia animali in Liguria”. Archeologia medievale, 8 (1981), pp. 239-246. BLOCH, Marc – Les caractères originaux de l’histoire rurale française. 2ª ed., vol. I. Paris: Armand Colin,1953. CABRAL, Francisco Caldeira; TELLES, Gonçalo Ribeiro – A árvore em Portugal. Lisboa: Assírio & Alvim, 1999. CABRERA MUÑOZ, Emilio – “El bosque, el monte y su aprovechamiento en la España del Sur durante la Baja Edad Media”. in PÉREZ-EMBID, Javier (ed.) – La Andalucía medieval. Actas “I Jornadas de historia rural y medio ambiente” (Almonte, 23-25 Maio 2000). Huelva: Universidad de Huelva – Servicio de Publicaciones, 2002, pp. 249-272. CARMONA RUIZ, María Antonia – La ganadería en el reino de Sevilla durante la Baja Edad Media. Sevilha: Diputación de Sevilla, 1998. CASTRO, Armando de – A evolução económica de Portugal dos séculos XII a XV. Vol. I. Lisboa: Portugália Editora, 1964. – “Montado”. in SERRÃo, Joel (dir.) – Dicionário de História de Portugal. Vol. III. Lisboa: Iniciativas Editoriais, 1968, p. 100. – “Pinhal de Leiria”. in SERRÃo, Joel (dir.) – Dicionário de História de Portugal. Vol. III. Lisboa: Iniciativas Editoriais, 1968, pp. 385-386. CHARBONNIER, Pierre – Une autre France. La seigneurie rurale en Basse Auvergne du XIVe au XVIe siècle. Vol. I e II. Clermont-Ferrand: Publications de l’Institut d’Études du Massif Centrale – Faculté des Lettres et Sciences Humaines de l’Université de Clermond-Ferrand, 1980. CLEMENTE RAMOS, Julián – “La ganadería porcina de Jarandilla de la Vera a mediados del siglo XV”. in FONSECA, Luís Adão; AMARAL, Luís Carlos; SANTOS, Maria Fernanda Ferreira (ed.) – Os reinos ibéricos na Idade Média. Livro de homenagem ao Professor Doutor Humberto Carlos Baquero Moreno. Vol. II. Porto: Livraria Civilização Editora, 2003, pp. 743-749. – La economía campesina en la Corona de Castilla (1000-1300). Barcelona: Crítica, 2004. COELHO, Maria Helena da Cruz – O Baixo Mondego nos finais da Idade Média (Estudo de história rural). Vol. I. Coimbra: Imprensa Nacional – Casa da Moeda, 1989. CONDE, Manuel Sílvio Alves – Uma paisagem humanizada. O Médio Tejo nos finais da Idade Média. Vol. I. Cascais: Patrimonia, 2000. CORRAO, Pietro – “Per una storia del bosco e dell’incolto in Sicilia fra XI e XIII secolo”. in ANDREOLLI, Buno; MONTANARI, Massimo (ed.) – Il bosco nel Medioevo. Bolonha: CLUEB, 1988, reimp. de 1990, pp. 349-369. CORREIA, Clara Pinto – Portugal animal. Fotografias de António José Cidadão. Lisboa: Relógio D’Água, 2000. DELORT, Robert – Les animaux ont une histoire. Paris: Seuil, 1984. DÉMIANS D’ARCHIMBAUD, Gabrielle – Les fouilles de Rougiers (Var). Contribution à l’archéologie de l’habitat rural médiéval en Pays méditerranéen, Paris: CNRS, 1980. DEVÈZE, Michel – La vie de la forêt française au XVIe siècle. Vol. I. Paris: S.E.V.P.E.N., 1961. DUBY, Georges – L’économie rurale et la vie des campagnes dans l’Occident médiéval (France, Angleterre, Empire, IXe – XVe siècles). Essai de synthèse et perspectives de recherche. Vol. I. Paris: Aubier, 1962. DURAND, Robert – Les campagnes portugaises Entre Douro et Tage aux XIIe et XIIIe siècles. Paris: Centre Culturel Portugais, 1982. DUVAL-ARNOULD, Louis – “Les ressources de la forêt royale de Retz et leur place dans l’économie de l’abbaye de Longpont”. in L’économie cistercienne. Géographie – Mutations du Moyen Âge aux temps moderns. Publications de la Commission d’Histoire de Flaran, 3. Auch: Comité Départemental du Tourisme de Gers, 1983, pp. 189-196. FERNANDES, João Luís Jesus – O homem, o espaço e o tempo no Maciço Calcário Estremenho. O olhar de um geógrafo. Lisboa - Coimbra: Ed. Colibri - Faculdade de Letras da Universidade de Coimbra, 2000. FRANCO, João do Amaral – “Carvalho”, Verbo. Enciclopédia luso-brasileira de cultura. Vol. 4. Lisboa: Verbo, [1992], col. 1247-1249. FRÍAS ZURITA, Victor – “El medio natural en una sociedad señorializada: composición, explotación y apropriación del inculto en la Catalunya del Noreste (siglos X-XIII)”. in Clemente Ramos,Julián (ed.) – El medio natural en la España medieval. Actas del I congreso de ecohistoria e historia medieval. Cáceres: Universidad de Extremadura, 2001, pp. 277-299. GALETTI, Paola – “Bosco e spazi incolti nel territorio piacentino durante l’Alto Medioevo”. in Andreolli, Bruno; Montanari,Massimo (eds.) – Il bosco nel Medioevo. Bolonha: Casa Editrice Clueb, 1990, pp. 199-221. GONÇALVES, Iria – O património do mosteiro de Alcobaça nos séculos XIV e XV. Lisboa: FCSH-UNL, 1989. – “Traços da paisagem rural nas terras de Alcobaça (séculos XIV-XV)”. in Tarouca e Cister. Espaço, espírito e poder. Actas, Setembro 2002. Tarouca: Câmara Municipal de Tarouca, 2004, pp. 367-388. – “Sobre o coberto arbóreo da Beira Interior nos finais da Idade Média”. in Estudos em homenagem ao Professor Doutor José Amadeu Coelho Dias. Vol. I. Porto: Faculdade de Letras da Universidade do Porto, 2006, pp. 321-350. – “A alimentação”. in MATTOSO, José (dir.) – História da vida privada em Portugal. Vol. I – A Idade Média. Coord. por Bernardo Vasconcelos e SOUSA. Lisboa: Temas e Debates - Círculo de Leitores, 2010, pp. 226-259. – “A árvore na paisagem rural do Entre-Douro-e-Minho”. in Por terras de Entre-Douro-e-Minho com as inquirições de Afonso III. Porto: CITCEM – Faculdade de Letras da Universidade do Porto – Ed. Afrontamento, 2012, pp. 49-84. GRAND, Roger; DELATOUCHE, Raymond – L’agriculture au Moyen Âge. De la fin de l’Empire romain au XVIe siècle. Vol. II, de Savoy, Émile (dir.) – L’agriculture à travers les âges. Paris: Ed. de Boccard, 1950. GRESSER, Pierre – “Nature et montant des recettes forestières du comté de Bourgogne au XIVe siècle d’après les comptes de gruerie”. in Dessert,Andrée Corvol (ed.) – Les forêts d’Occident du Moyen Âge à nos jours. Actes des XXIVes Journées internationales d’histoire de l’abbaye de Flaran. 6, 7, 8 septembre 2002. Toulouse: Presses Universitaires du Mirail, 2004, pp. 13-38. GUADALAJARA SOLERA, Simón – Lo pastoril en la cultura extremeña. Cáceres: Institución Cultural El Brocense, 1984. HERCULANO, Alexandre – História de Portugal desde o começo da monarquia até ao fim do reinado de Afonso III. Ed. crítica de José MATTOSO, vol. IV. Lisboa: Livraria Bertrand, 1980. HIGOUNET, Charles – “Les forêts de l’Europe Occidentale du Ve au XIe siècle”. in Paysages et villages neufs du Moyen Âge. Bordéus: Fédération Historique du Sud Ouest, 1975, pp. 37-62. KLEIN, Julius – La Mesta. Estudio de historia económica espanhola. 1273-1836. [3ª ed.]. Madrid: Alianza Editorial, 1981. LAUTENSACH, Hermann – “A cobertura vegetal”. in Ribeiro, Orlando; Lautensach,Hermann – Geografia de Portugal. Org., comentários e actualização por Suzanne DAVEAU. Vol. II, O ritmo climático e a paisagem. Lisboa: Ed. João Sá da Costa, 1988, pp. 539-575. MARTÍN GUTIÉRREZ, Emilio – Paisajes, ganadería y medio ambiente en las comarcas gaditanas. Siglos XIII al XVI. Cadiz: Universidad de Cadiz – Servicio de Publicaciones, 2015. MAZZI Maria Serena; RAVEGGI, Sergio – Gli uomini e le cose nelle campagne fiorentine del Quattrocento. Florença: Olschki, 1983. MONTANARI, Massimo – “Gli animali e l’alimentazione umana”. in L’uomo di fronte al mondo animale nell’Alto Medioevo. XXXI Settimani di studi del Centro Italiano di Studi sull’ Alto Medioevo. Tomo I. Spoleto: Centro italiano di studi sull'alto medioevo, 1985, pp. 619-663. – Alimentazione e cultura nel Medioevo. Roma – Bari: Editiri Laterza, 1988. – “Dal bosco alla stalla. Il maiale nel Medioevo” in Uomini, terre, boschi nell’Occidente medievale. Catania: Cooperativa Universitaria Catanese di Magistero, 1992, pp. 173-182. – “Estruturas de produção e sistemas alimentares”. in MONTANARI, Massimo; FLANDRIN, Jean-Louis (dir.) – História da alimentação.Vol. 1 - Dos primórdios à Idade Média. Trad. de Maria da Graça Pinhão. Lisboa: Terramar, 1998, pp. 251-259. NATIVIDADE, Joaquim Vieira – A região de Alcobaça. Algumas notas para o estudo da sua agricultura, população e vida rural. Obras várias. Vol. I. Alcobaça: s.n., s. d. NATIVIDADE, Joaquim Vieira; MACEDO, Jorge Borges – “As instituições e as técnicas na história regional”. in SILVA, Carlos da, ALARCÃO, Alberto; CARDOSO,António Poppe Lopes – A região a Oeste da Serra dos Candeeiros. Estudo económico-agrícola dos concelhos de Alcobaça, Nazaré, Caldas da Rainha, Óbidos e Peniche. Lisboa: Fundação Calouste Gulbenkian – Centro de Estudos de Economia Agrária, 1961, pp. 63-95. PENTEADO, Pedro – “Rendas e fazendas do mosteiro de Alcobaça durante a comenda do infante D. Afonso (1530-1536)”. in Actas Cister. Espaços. Territórios. Paisagens. Colóquio internacional, 16-20 de Junho de 1998, Mosteiro de Alcobaça. Vol. II – Economia e sociedade. Espiritualidade. Arquitectura. Lisboa: IPPA, 2000, pp. 89-98. PÉREZ-EMBID, Javier – “El Císter hispano y la ganadería”. in Arízaga Bolumburu, Beatriz et alii (ed.) – Mundos medievales: espacios, sociedades y poder. Homenaje al Profesor José Ángel García de Cortázar y Ruiz de Aguirre.T. II. Santander: PUbliCan – Ediciones de la Universidad de Cantabria, 2012, pp. 1769-1785. REDON, Odile – “Les usages de la viande en Toscanie au XVIe siècle”. in Manger et boire au Moyen Âge. Actes du colloque de Nice (15-17 octobre 1982). T. 2 – Cuisine, manières de table, régimes alimentaires. Nice: Publications de la Faculté des Lettres et de Sciences Humaines de Nice, 1984, pp. 121-130. RIBEIRO, Orlando – Portugal, o Mediterrâneo e o Atlântico. Esboço de relações geográficas. 2ª ed. Lisboa: Sá da Costa, 1963. – “O manto vegetal”. in Ribeiro, Orlando; Lautensach,Hermann – Geografia de Portugal. Org., comentários e actualização por Suzanne DAVEAU. Vol. II, O ritmo climático e a paisagem. Lisboa: Ed. João Sá da Costa, 1988, pp. 577-584. RODRIGUES, Ana Maria Seabra de Almeida – “A produção agro-pecuária”. in SERRÃO, Joel; MARQUES, A. H. de Oliveira (dir.) – Nova História de Portugal. Vol. V – Portugal do Renascimento à crise dinástica. Coord. por João José Alves DIAS. Lisboa: Ed. Presença, 1998, pp. 165-181. SANTIARD, Marie-Thérèse – “La glandée dans les forêts ducales au XIVe siècle d’après les comptes de gruerie”. Annales de Bourgogne XLVI (Out.-Dez. 1974), pp. 193-234. SCLAFERT, Thérèse – Cultures en Haute Provence. Deboissement et pâturage au Moyen Âge. Paris: S.E.V.P.E.N., 1959. SEQUEIRA, Joaquim Pedro Fragoso de – “Memória sobre as azinheiras, sovereiras e carvalhos da província do Alentejo, onde se trata da sua cultura, e usos, e dos melhoramentos, que no estado actual podem ter”. in Memórias económicas da Academia Real das Ciências de Lisboa, para o adiantamento da cultura, das artes e da indústria em Portugal e suas conquistas (1789-1815). t. II, dirig. por José Luís CARDOSO. Lisboa: Banco de Portugal, 1991, pp. 253-271. SILVA, Carlos da, ALARCÃO, Alberto; CARDOSO,António Poppe Lopes – A região a Oeste da Serra dos Candeeiros. Estudo económico-agrícola dos concelhos de Alcobaça, Nazaré, Caldas da Rainha, Óbidos e Peniche. Lisboa: Fundação Calouste Gulbenkian – Centro de Estudos de Economia Agrária, 1961. TRINDADE, Maria José Lagos – “A vida pastoril e o pastoreio em Portugal nos séculos XII a XVI”. in Estudos de história medieval e outros. Lisboa: História & Crítica, 1981, pp. 1-95. VICENTE, Maria da Graça – Povoamento e propriedade entre o Zêzere e o Tejo (séc. XII-XIV). Lisboa: Ed. Colibri, 2015.